2016
DOI: 10.3233/bme-161589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crosslinking methods on the structure and biocompatibility of polyvinyl alcohol/gelatin cryogels

Abstract: In this study, polyvinyl alcohol (PVA) and gelatin based cryogels were prepared by crosslinking chemically or physically for tissue engineering applications. Different PVA/Gelatin ratios (100:0, 90:10, 70:30, 50:50) and crosslinking methods have been used to prepare cryogels; chemical and physical structure of the prepared matrices were analysed by FTIR and SEM; swelling and degradation profiles were followed. Chemical and physical crosslinking was obtained by using glutaraldehyde as crosslinker and by applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Glutaraldehyde was used as the cross-linker, which has been used in many former studies although the risk of its cytotoxicity and its influence on biodegradability should not be overlooked (Ceylan, Gokturk & Bolgen, 2016;Dinescu et al, 2013;Ulubayram, Aksu, Gurhan, Serbetci & Hasirci, 2002;Yang, Chen, Chen & Lin, 2005). PVA were further combined to modify the mechanical properties of GCH composite scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Glutaraldehyde was used as the cross-linker, which has been used in many former studies although the risk of its cytotoxicity and its influence on biodegradability should not be overlooked (Ceylan, Gokturk & Bolgen, 2016;Dinescu et al, 2013;Ulubayram, Aksu, Gurhan, Serbetci & Hasirci, 2002;Yang, Chen, Chen & Lin, 2005). PVA were further combined to modify the mechanical properties of GCH composite scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Functional group tests using FTIR showed that the PVA and alginate nanofibers were stable at an 8:2 ratio compared to fibers with only alginate or PVA ( Figure-2 ). Such polymer mixtures are reported to have biocompatible properties and stable functional groups [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology of PVA‐CNDs fluorescent hydrogel was more compact than pure PVA hydrogel. The pure PVA hydrogels formed by entanglement of PVA chains, presenting disordered pores . Displaying hydrogels with various sizes of pore structures in SEM images implied that the network structure formed by the cross‐linking of PVA and CNDs was more uniform and smaller, so that the hydrogel had excellent mechanical properties .…”
Section: Resultsmentioning
confidence: 99%
“…The pure PVA hydrogels formed by entanglement of PVA chains, presenting disordered pores. [62,63] Displaying hydrogels with various sizes of pore structures in SEM images implied that the network structure formed by the cross-linking of PVA and CNDs was more uniform and smaller, so that the hydrogel had excellent mechanical properties. [2,64] Besides, PVA-CNDs hydrogels exhibited interconnected and relatively ordered porous network structures.…”
Section: Morphology Analysismentioning
confidence: 99%